A variable-length Cell Transmission Model for road traffic systems. (December 2018) - Canudas-de-Wit, Carlos; Ferrara, Antonella
Abstract: In this paper we propose a new aggregated Variable-Length cell transmission Model (VLM) for traffic systems consisting of only three lumped state variables. The first two state variables are the lumped (or averaged) densities associated with the two cells of variable length into which the considered road section is subdivided. These cells are, respectively, a downstream congested cell, of length l, and an upstream free cell, of length L - l, L being the total length of the section. The third state, namely l, describes the position of the congestion wave front. The paper, apart from providing the new traffic model formulation, also investigates several mathematical properties of this model, ensuring the consistency with respect to the inherent mass (or vehicle) conservation law. Two case studies, a ring road and a urban road with traffic lights, are considered to assess the proposed model validity also relying on simulation evidence.